Personality assessment with Temperament and Character Inventory in Parkinson's disease. (October 2022) - Boussac, Mathilde; Arbus, Christophe; Colin, Olivier; Laurencin, Chloé; Eusebio, Alexandre; Hainque, Elodie; Corvol, Jean Christophe; Versace, Nathalie; Rascol, Olivier; Rousseau, Vanessa; Harroch, Estelle; Ory-Magne, Fabienne; et al.
Abstract: Introduction: There is a growing interest in personality evaluation in Parkinson's disease (PD), following observations of specific temperaments in PD patients. Therefore, our objective was to evaluate personality dimensions from the Temperament and Character Inventory (TCI) in a cohort of fluctuating PD patients considered for deep brain stimulation. Methods: Fluctuating PD patients from the PREDISTIM cohort were included. Description of TCI dimensions and comparison with a French normative cohort were performed. Pearson correlations between TCI dimensions and motor, behavioral and cognitive variables were investigated. Structural and internal consistency analysis of the TCI were further assessed. Results: The 570 PD patients presented significant higher scores in Harm Avoidance, Reward Dependence, Persistence, Self-Directedness and Cooperativeness and significant lower scores in Self-Transcendence compared to the French normative cohort; only Novelty Seeking scores were not different. Harm Avoidance and Self-directedness scores were correlated with PDQ-39 total, HAMD, HAMA scores, and anxiolytic/antidepressant treatment. Novelty Seeking scores were correlated with impulsivity. Pearson correlations between TCI dimensions, principal component analysis of TCI sub-dimensions and Cronbach's alpha coefficients showed adequate psychometric proprieties. Conclusion: The TCI seems to be an adequate tool to evaluate personality dimensions in PD with good structural and internal consistencies. These fluctuating PD patients also have specific personality dimensions compared to normative French population. Moreover, Harm Avoidance and Self-Directedness scores are associated with anxio-depressive state or quality of life and, and Novelty Seeking scores with impulsivity. Highlights: TCI psychometric proprieties are adequate to evaluate personality in PD. Fluctuating PD patients have a specific personality but not personality disorders. Novelty Seeking scores are higher in advanced PD patients compared to De Novo ones. Harm Avoidance and Self-Directedness are related to anxio-depressive state and Quality of Life. Novelty Seeking is associated with higher impulsivity and compulsive symptoms.